A Study on Banking: What Discriminates Loyal and Disloyal Customers of Banking Industry in Punjab? - Kaur, Manpreet (Gyan Management Journal, 2015)
Banking sector has undergone a drastic change due to increased competition induced by liberalisation, privatisation and globalisation. All the banks are rushing towards acquiring more and m_ore customers which has resulted in less loyalty among customers. To survive in this highly competitive environment, banks need to focus on customer retention as cost of acquiring a new customer is more than cost of retaining an existing one. This can be done only if banks are able to identify the factors which discriminate loyal and disloyal customers. Hence, in the present study, disloyal customers are identified as those switching their current primary bani< because of dissatisfaction with services. Comparison of disloyal customers is made with loyal customers to identify the factors, dissatisfaction with which may lead to switching behaviour of customers. The research provides directions to commercial banks as to which service quality dimension requires attention to increase customer retention.
Keywords: Bank Switching; Loyalty; Commercial Banks; Switchers; DiscriminantAnalysis